Europe 2020: The EU Commission and Political Entrepreneurship - Silander, Daniel (International Studies. Interdisciplinary Political and Cultural Journal, 2024)
This study deals with the European Commission and Communication Europe 2020, which was a result of the global economic crisis of 2007–2008 and forward. Europe 2020 was an initiative to deal with the crisis by promoting smart, sustainable, and inclusive growth. The Commission addressed the crisis as an existential threat to Europe, but also as a window of opportunity to build a new prosperous region. This study explores the political entrepreneurial efforts taken by the Commission as well as assesses the outcome of reforms implemented. The Commission has achieved many targets, although some challenges remain unsolved.